Probabilitas Ketepatan Biaya Dan Waktu Dengan Metode Monte Carlo Pada Konsep Earned Value Untuk Proyek Jalan - Agustin, Chinta Eva; Soetjipto, Jojok Widodo; Hasanudin, Akhmad (Journal of Applied Civil Engineering and Infrastructure Technology, 2023)
Planning and implementing a construction project involves several factors that must be considered including cost, quality and time. This is the main challenge in a project by controlling costs and time without reducing the quality of work. In this study the case of the construction of the Bts Road Reconstruction Package and Widening Package. Bojonegoro-Pajeng City Of Sta 28 + 230 - 32 + 230 is deemed necessary to carry out a cost and time control with the Concept of Earned Value and Monte Carlo to look for more indicators in analyzing the project so that an optimal cost and time estimate is obtained. There are 3 (three) parameters used in the result value concept, namely ACWP, BCWS, BCWP.The analysis was performed by looking for variations in the calculation manually and using the help of Crystal Ball software. The monitoring result with the Result Value Concept is the comparison of the BCWP value below the ACWP value which proves the project is experiencing fund swelling, and the BCWS value above the BCWP value proves the project is experiencing delays. While the results of monitoring the Result Value Concept using the Monte Carlo method produce the maximum and minimum value of all parameters so that it can be used as a reference for the contractor to determine the rescheduling time for the rest of the project so that the costs and time for the project are in accordance with the planning.